DLL1 haploinsufficiency in prenatal brain anomalies: a retrospective analysis of 6q terminal deletions - Ge, Tingting; Lin, Xiaojuan; Tian, Xinyuan; Song, Xiaoyu; Zhou, Bingbo; Hui, Ling; Wang, Xiaozhuan; Zhang, Zhiqiang; Zhang, Chuan (Frontiers in Genetics, 2025)
Objective6q terminal deletion is a rare genetic cause of prenatal brain anomalies. We evaluated five cases of cerebral dysplasia within a familial context for genetic diagnosis. Aims to analyze prenatal brain abnormalities from 6q terminal deletion of DLL1 and support prenatal diagnosis and genetic counseling.MethodsA retrospective analysis was conducted on data from five families with fetal brain structural dysplasia, collected at Gansu Provincial Maternity and Child-care Hospital (Gansu Central Hospital) between January 2017 and April 2024. We applied copy number variation sequencing (CNV-Seq) and when negative, whole-exome sequencing (WES) to define genomic etiologies of prenatal brain anomalies.ResultsA total of 5 fetuses were included in this study. All fetuses exhibited a cerebellar diameter smaller than expected for their gestational age, as determined by US, 4/5 cases underwent MRI. In fetuses 1–4, CNV-Seq analysis identified heterozygous deletions of 1.74 Mb, 2.88 Mb, 0.72 Mb, and 21.99 Mb at the terminal region of chromosome 6q. In fetus 5, WES successfully identified the deletion that CNV-seq had missed, likely terminal coverage drop/binning limit.ConclusionFetuses with reduced transverse cerebellar diameter and ventriculomegaly should be evaluated for 6q terminal deletions involving DLL1; combining CNV-seq with reflex WES reduces missed diagnoses and informs counseling.